Tension pneumothorax, is it a really life-threatening condition? - Yoon, Jeong Seob (BioMed Central, 2013)
BACKGROUND: Tension pneumothorax is a life-threatening occurrence that is infrequently the consequence of spontaneous pneumothorax. The aim of this study was to identify the risk factors for the development of tension pneumothorax and its effect on clinical outcomes. METHODS: We reviewed patients who were admitted with spontaneous pneumothorax between August 1, 2003 and December 31, 2011. Electronic medical records and the radiological findings were reviewed with chest x-ray and high-resolution computed tomography scans that were retrieved from the Picture Archiving Communication System. RESULTS: Out of the 370 patients included in this study, tension pneumothorax developed in 60 (16.2%). The bullae were larger in patients with tension pneumothorax than in those without (23.8 ± 16.2 mm vs 16.1 ± 19.1 mm; P = 0.007). In addition, the incidence of tension pneumothorax increased with the lung bulla size. Fibrotic adhesion was more prevalent in the tension pneumothorax group than in that without (P = 0.000). The bullae were large in patients with fibrotic adhesion than in those without adhesion (35.0 ± 22.3 mm vs 10.4 ± 11.5 mm; P = 0.000). On multivariate analysis, the size of bullae (odds ratio (OR) = 1.03, P = 0.001) and fibrotic adhesion (OR = 10.76, P = 0.000) were risk factors of tension pneumothorax. Hospital mortality was 3.3% in the tension pneumothorax group and it was not significantly different from those patients without tension pneunothorax (P = 0.252). CONCLUSIONS: Tension pneumothorax is not uncommon, but clinically fatal tension pneumothorax is extremely rare. The size of the lung bullae and fibrotic adhesion contributes to the development of tension pneumothorax.